Pumpkin Seed Oil-Loaded Niosomes for Topical Application: 5α-Reductase Inhibitory, Anti-Inflammatory, and In Vivo Anti-Hair Loss Effects - Veerawat Teeranachaideekul; Warisara Parichatikanond; Varaporn Buraphacheep Junyaprasert; Boontida Morakul (MDPI AG, 2022)
Pumpkin seed oil (PSO)-loaded niosomes were prepared from Tween 20 and cholesterol by ethanol injection. Confocal microscopy showed better skin permeation and hair follicle accumulation of the niosomes compared to the PSO solution. The PSO-loaded niosomes inhibited 5α-reductase activity in DU-145 cells and hindered IL-6 activity in RAW 264.7 cells. These effects indicated the great potential of PSO-loaded niosomes to reduce hair loss. The hair scalp serum with PSO-loaded niosomes did not show irritation to reconstructed human skin. This formulation presented a significant decrease in the percentage of fallen hairs by 44.42% in the in vivo 60-second hair count experiment and a significant increase in the anagen to telogen (A/T) ratio (1.4-fold) in the TrichoScan® evaluation after 8 weeks of treatment compared to the initial conditions, indicating the promising efficacy of PSO-loaded niosomes as a natural alternative for anti-hair loss therapy.